2019
DOI: 10.1371/journal.pone.0216780
|View full text |Cite
|
Sign up to set email alerts
|

The proximal experience of awe

Abstract: Research on awe has grown exponentially in recent decades; however, few studies have considered whether awe-inspiring experiences also inspire other emotions. In two studies, we explored whether interventions targeting awe also evoke other discrete emotions. Additionally, we considered two constructs that may be associated with increases in each emotion—self-relevant thoughts and connectedness. In Study 1, we manipulated awe in virtual reality and examined the potential effects of a prototypical awe experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 51 publications
(122 reference statements)
3
64
1
Order By: Relevance
“…Positive awe enhances a sense of connection to a particular person (e.g., a friend) or to people in general (Shiota et al, 2007;Van Cappellen and Saroglou, 2012;Krause and Hayward, 2015;Stellar et al, 2017;Nelson-Coffey et al, 2019). In an American sample, positive awe was found to decrease self-focused attention and strengthen the feeling of being included in a community .…”
Section: Introductionmentioning
confidence: 92%
“…Positive awe enhances a sense of connection to a particular person (e.g., a friend) or to people in general (Shiota et al, 2007;Van Cappellen and Saroglou, 2012;Krause and Hayward, 2015;Stellar et al, 2017;Nelson-Coffey et al, 2019). In an American sample, positive awe was found to decrease self-focused attention and strengthen the feeling of being included in a community .…”
Section: Introductionmentioning
confidence: 92%
“…For example, Anderson et al (2018) found that experiencing awe in nature and outdoor activities improved well-being in military veterans and at-risk youth. More recently, some research has found that awe can promote other positive emotions such as compassion, gratitude, and optimism (Nelson-Coffey et al, 2019) and decrease anxiety during waiting periods for uncertain news (Rankin et al, 2019).…”
Section: Why Awe?mentioning
confidence: 99%
“…Awe has also been shown to provide spiritual benefits. Awe promotes a sense of connectedness (Nelson-Coffey et al, 2019), a willingness to travel to spiritual destinations such as Tibet (Van Cappellen & Saroglou, 2012), and prompts people to look beyond mundane concerns (Chirico & Yaden, 2018;Jiang et al, 2018;Shiota et al, 2017;Yaden et al, 2016).…”
Section: Why Awe?mentioning
confidence: 99%
See 2 more Smart Citations